Design and development of OTRmail security engine for thunderbird - Wang, Derong (2010)
Electronic mail has become an important mode of communication, thus security and privacy of correspondence has become an increasing concern. It is also noted that emails which are sent in clear are easily eavesdropped by intermediate nodes forwarding the emails. To overcome this issue, secure email solutions are being used. Currently, secure email solutions use either Secure/Multipurpose Internet Mail Extension (S/MIME), Pretty Good Privacy (PGP) or OpenPGP protocols. These protocols are not suitable for personal communication as they use long-lived encryption keys, digital signatures and complex key distributions. Hence, the use of Off-The-Record Mail (OTRmail) protocol is suggested.